Two-path all-pass based half-band infinite impulse response decimation filters and the effects of their non-linear phase response on ECG signal acquisition. (January 2017) - Eminaga, Yaprak; Coskun, Adem; Kale, Izzet
Highlights: Very low-complexity decimation filters for ECG signal digitization are proposed. Filters' nonlinear phase effects are analysed with and without phase compensation. Power consumption and filter performance are superior to the existing ones. No notable distortion is observed on the ECG signal with or without phase correction. Abstract: This paper is based on the novel use of a very high fidelity decimation filter chain for Electrocardiogram (ECG) signal acquisition and data conversion. The multiplier-free and multi-stage structure of the proposed filters lower the power dissipation while minimizing the circuit area which are crucial design constraints to the wireless non-invasive wearable health monitoring products due to the scarce operational resources in their electronic implementation. The decimation ratio of the presented filter is 128, working in tandem with a 1-bit 3 rd order Sigma Delta (ΣD) modulator which achieves 0.04 dB passband ripples and −74 dB stopband attenuation. The work reported here investigates the non-linear phase effects of the proposed decimation filters on the ECG signal by carrying out a comparative study after phase correction. It concludes that the enhanced phase linearity is not crucial for ECG acquisition and data conversion applications since the signal distortion of the acquired signal, due to phase non-linearity, is insignificant for both original and phase compensated filters. To the best of the authors' knowledge, being free of signal distortion is essential as this might lead to misdiagnosis as stated in the state of the art. This article demonstrates that with their minimal power consumption and minimal signal distortion features, the proposed decimation filters can effectively be employed in biosignal data processing units.